The gut microbiota metabolite indole alleviates liver inflammation in mice. Issue 12 (15th June 2018) - Beaumont, Martin; Neyrinck, Audrey M.; Olivares, Marta; Rodriguez, Julie; de Rocca Serra, Audrey; Roumain, Martin; Bindels, Laure B.; Cani, Patrice D.; Evenepoel, Pieter; Muccioli, Giulio G.; Demoulin, Jean‐Baptiste; Delzenne, Nathalie M.
ABSTRACT: The gut microbiota regulates key hepatic functions, notably through the production of bacterial metabolites that are transported via the portal circulation. We evaluated the effects of metabolites produced by the gut microbiota from aromatic amino acids (phenylacetate, benzoate, p ‐cresol, and indole) on liver inflammation induced by bacterial endotoxin. Precision‐cut liver slices prepared from control mice, Kupffer cell (KC)‐depleted mice, and obese mice (ob/ob) were treated with or without LPS and bacterial metabolites. We observed beneficial effects of indole that dose‐dependently reduced the LPS‐induced up‐regulation of proinflammatory mediators at both mRNA and protein levels in precision‐cut liver slices prepared from control or ob/ob mice. KC depletion partly prevented the antiinflammatory effects of indole, notably through a reduction of nucleotide‐binding domain and leucine‐rich repeat containing (NLR) family pyrin domain‐containing 3 (NLRP3) pathway activation. In vivo, the oral administration of indole before an LPS injection reduced the expression of key proteins of the NF‐KB pathway and downstream proinflammatory gene up‐regulation. Indole also prevented LPS‐induced alterations of cholesterol metabolism through a transcriptional regulation associated with increased 4β‐hydroxycholesterol hepatic levels. In summary, indole appears as a bacterial metabolite produced from tryptophan that is able to counteract the detrimental effects of LPS in the liver. Indole could be a new target to develop innovative strategies to decrease hepatic inflammation.—Beaumont, M., Neyrinck, A. M., Olivares, M., Rodriguez, J., de Rocca Serra, A., Roumain, M., Bindels, L. B., Cani, P. D., Evenepoel, P., Muccioli, G. G., Demoulin, J.‐B., Delzenne, N. M. The gut microbiota metabolite indole alleviates liver inflammation in mice. FASEB J. 32, 6681–6693 (2018). www.fasebj.org